2018
DOI: 10.1093/cid/ciy182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre-exposure Prophylaxis for the Prevention of Human Immunodeficiency Virus Infection on Sexual Risk Behavior in Men Who Have Sex With Men: A Systematic Review and Meta-analysis

Abstract: Findings highlight the importance of efforts to minimize STIs among PrEP users and their sexual partners. Monitoring of risk compensation among MSM in the context of PrEP scale-up is needed to assess the impact of PrEP on the sexual health of MSM and to inform preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
278
1
18

Year Published

2019
2019
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(322 citation statements)
references
References 32 publications
25
278
1
18
Order By: Relevance
“…A recent systematic review of PrEP studies found that condom use tends to fall and STI incidence rises among PrEP users over time, as they become more comfortable relying on the intervention (Traeger et al . ). The optimistic scenarios outlined here remain an unproven future, much like the scenarios expressed by those who were concerned about PrEP.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…A recent systematic review of PrEP studies found that condom use tends to fall and STI incidence rises among PrEP users over time, as they become more comfortable relying on the intervention (Traeger et al . ). The optimistic scenarios outlined here remain an unproven future, much like the scenarios expressed by those who were concerned about PrEP.…”
Section: Resultsmentioning
confidence: 97%
“…So far, a reduction in STIs has not been observed among PrEP users or in international jurisdictions that have embraced PrEP (Centers for Disease Control and Prevention, , The Kirby Institute, , Traeger et al . ). However, there is growing evidence for the optimistic position that PrEP can engage users in regular sexual health care and significantly reduce the fear of HIV (Hughes et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another concern raised in relation to PrEP refers to “risk compensation,” or a shift towards more risky sexual behaviour triggered by perceptions of decreased HIV risk . A systematic review and meta‐analysis of seventeen open‐label studies found that PrEP among MSM was associated with a decrease in overall condom use but no increase in HIV . However, these changes in sexual behaviour may increase the chances of acquiring STIs other than HIV .…”
Section: Introductionmentioning
confidence: 99%